2017
DOI: 10.1080/24699322.2017.1282044
|View full text |Cite
|
Sign up to set email alerts
|

Three-dimensional fluoroscopic navigation-assisted surgery for tumors in patients with tumor-induced osteomalacia in the bones

Abstract: Navigation-assisted surgery using a 3D fluoroscopy-based navigation system is effective for tumors in patients with TIO.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
6
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 15 publications
(27 reference statements)
1
6
0
1
Order By: Relevance
“…It does not make sense to compare the delicate differences between our cases and those reported in various institutes because other cases are so scattered. TIO tumors in the spine are even more rare, with only 18 cases reported in the literature before the current study . Our nine spine cases enriched the current limited experience of this peculiar type of TIO.…”
Section: Discussionsupporting
confidence: 71%
See 1 more Smart Citation
“…It does not make sense to compare the delicate differences between our cases and those reported in various institutes because other cases are so scattered. TIO tumors in the spine are even more rare, with only 18 cases reported in the literature before the current study . Our nine spine cases enriched the current limited experience of this peculiar type of TIO.…”
Section: Discussionsupporting
confidence: 71%
“…TIO tumors in the spine are even more rare, with only 18 cases reported in the literature before the current study. (17)(18)(19) Our nine spine cases enriched the current limited experience of this peculiar type of TIO. Despite the small sample size, we observed unusually poor outcomes of these cases, with more than two-thirds of tumors being persistent or recurrent.…”
Section: Discussionmentioning
confidence: 58%
“…[1–3] Diffuse bone pain caused by poor bone mineralization is the most frequent symptom in these patients suffering from TIO. [1–3,11,12] To date, less than 500 cases have been reported in literature, thus the majority of clinicians are less aware of this disease. In addition, the clinical course of TIO is often slow, and the volume of pathogenic tumor is commonly very small.…”
Section: Discussionmentioning
confidence: 99%
“…Based on our review of the literature on PubMed, the average time from onset of symptoms to a confirmed diagnosis of TIO often exceeds 2.5 years. [1–3,811,17,18] Definitive treatment is further delayed by an average of 5 years due to inability to find the underlying tumor due to the characteristics of being small and slow growing and being located in particular or atypical sites. [811,17,18] Typical laboratory findings include hyperphosphaturia, elevated alkaline phosphatase, and low serum 1,25-dihydroxy vitamin D in literature, respectively.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation